Identification of blaIMI-mediated carbapenem-resistant Enterobacter from a duck farm in China - Hong-hao HUANG; Yi-xing LU; Su-juan WU; Zhen-bao MA; Dong-ping ZENG; Zhen-ling ZENG (Journal of Integrative Agriculture, 2023)
Carbapenem- and colistin-resistant Enterobacter has been a clinical and therapy problem in recent years. Here, we report the carbapenem- and colistin-resistant Enterobacter harboring blaIMI isolated from intestinal samples and the environment of a duck farm in China. Four blaIMI-positive Enterobacter isolates were resistant to carbapenem and colistin. Three blaIMI subtypes were detected in different molecular categories of Enterobacter. The detection of the various IMI producers highlights the diversity of carbapenemases in a duck farm. Whole-genome sequencing demonstrated the blaIMI genes were present in chromosomes or plasmids in these strains. The conjugation experiment demonstrated the ability of blaIMI-carrying plasmid to transmit horizontally. The molecular evolution characteristics were examined through comparative genetic analysis. The study demonstrated the presence of chromosomal and plasmid blaIMI and the blaIMI-carrying plasmid exhibits a horizontal transmission between Enterobacter and Escherichia coli C600. The similar genetic content was discovered between two blaIMI-16-positive Enterobacter asburiae. In addition, a blaIMI-16-carrying plasmid is an IncFII(Yp) plasmid, and a substantial amount of mobile genetic elements were identified around blaIMI-16. The IS-like elements and IncFII(Yp) plasmid are significant in the propagation of blaIMI. Our study provides evidence for the transmission of diverse blaIMI genes in China and supplies additional reference data for blaIMI-positive antimicrobial-resistant Enterobacter. Routine surveys of blaIMI-positive Enterobacter from animal-raising environments must be given more focus.